Serum D-Dimer in the Diagnosis of Periprosthetic Knee Infection: Where Are We Today? - Pannu, Tejbir S.; Villa, Jesus M.; Riesgo, Aldo M.; Patel, Preetesh D.; Barsoum, Wael K.; Higuera-Rueda, Carlos A. (The Journal of Knee Surgery, 2020)
Periprosthetic joint infection (PJI) continues to impact a remarkable number of patients who undergo total knee arthroplasty (2.0–2.1%). Substantial efforts to curtail these rates have been seen in the past decade including various attempts to reach a clear definition of PJI that the orthopaedic community could adopt as a gold standard. The Musculoskeletal Infection Society (MSIS) criteria, slightly modified by the International Consensus Meeting (ICM), has gained widespread acceptance and it is a step closer to that goal. Research on markers such as serum cross-linked D-fragments (D-dimer) seems promising in the diagnosis of infection. In the setting of PJI, a recent publication has established a threshold of 850 ng/mL as the optimal cutoff value for serum D-dimer. Therefore, our objective is to present a summary of the current literature on the changing indications of D-dimer and its rising importance in the setting of PJI. Serum D-dimer has been shown to outperform other conventional tests such as erythrocyte sedimentation rate and C-reactive protein that have been a major part of the ICM criteria and it has been included in the newly proposed diagnostic criteria for PJI that correctly diagnoses infection in 95.5% of septic patients (overall sensitivity: 97.7%, specificity: 99.5%). In comparison with the ICM and MSIS infection definitions, the new criteria revealed a higher sensitivity (97.7 vs. 86.9% and 97.7 vs. 79.3%, respectively), while specificity was similar. In conclusion, high D-dimer levels in primary or revision knee arthroplasty seem indicative of diagnosis of PJI. However, future studies are warranted to conclusively support the routine use of this marker and to validate the performance of the newly developed PJI diagnostic criteria under different clinical scenarios.
Keywords: serum D-dimer; markers; periprosthetic joint infection; PJI; total knee arthroplasty